DISKURSUS KEABSAHAN AL-QIRÃâÃT AL-âASHR SEBAGAI BACAAN MUTAWÃTIR - Muzammil, Iffah (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2015)
Ten qirÃ¢âah belongs to the ten Imams of Qurâanic recitaters. It composes seven Imams who are remarkably recognized in Muslim traditions mainly introduced by Ibn MujÃ¢hid (245- 324 H), with three additional Imams, AbÃ» Jaâfar al-QaâqÃ¢â, AbÃ» YaâqÃ»b al-Haá¸ramÃ®, and Khalaf bin HishÃ¢m. Different from seven qirÃ¢âah that is officially approved (mutawÃ¢tir) by most of Muslim scholars, the existence of ten qirÃ¢âah is still debatable. Indeed, some of scholars classify it as poor qirÃ¢âah (shÃ¢dh). Five centuries later after Ibn MujÃ¢hidâs introduction on seven qirÃ¢âah, al-JazarÃ® (d. 833 H) argues some evidences on the validity of chain transmission (sanad) of the last three Imams. In the hand of al-JazarÃ®, the ten qirÃ¢âah is attested to be completely meeting a requirements of qirÃ¢âah such like, reliable chainâs transmission, compatible to rasm âUthmÃ¢nÃ®, and convenient to Arabic rules. Therefore, there is no reason to leave and refuse the last three Imams (ten qirÃ¢âah) in the Islamic tradition of Qurâanic recitation.